The International Politics of Natural Resources - Mikdashi, Zuhayr (Cornell University Press, 2019)
An impartial and shrewd observer here takes a close look at the major producers of today's most sought-after commodities. Mr. Mikdashi deals with the ever-shifting pattern of cooperation and antagonism between transnational enterprises (companies owned by corporations in developed countries and active in more than one nation) and their host governments, especially those in the developing world. Comparing operations in various countries and in various industries, he describes how governments and transnationals work, together and separately, to exploit market opportunities. Petroleum, copper, iron, sulfur, uranium, bauxite, and tin-these are among the resources he examines. He illuminates the policies, strategies, and relationships of the protagonists under different market and environmental conditions, discussing the relations among the governments themselves and the alliances they have formed (such as OPEC and CIPEC). Finally he offers suggestions for cooperative action that could both serve the needs of the less developed areas and promote international harmony. Practical in approach and original in concept, the book clarifies complex contemporary problems and points the way toward solving them.